Casting method for component in high-wear industrial environment and such casting
By using the titanium carbide composite zone formed by powder composition in a high wear industrial environment, the problems of reduced size and loss of function of components in a high wear environment are solved, and higher hardness and wear resistance are achieved, reducing production costs and time.
Patent Information
- Application Number
- CN202380052233.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-20
- Filing Date
- 2023-05-22
- Publication Date
- 2025-02-25
AI Technical Summary
In high wear industrial environments, existing components are prone to decrease in size due to wear during use, resulting in loss of function and degradation of performance, requiring frequent replacement of components, increasing costs and production time.
By using a powder composition during the casting process, including 55-80 wt.% reaction powder and 20-45 wt.% conditioning powder, a titanium carbide composite zone formed in situ in the molten main material, enhancing the hardness and wear resistance of the components.
Higher hardness and wear resistance of components in high wear environments are achieved, reducing manufacturing steps and production time, and reducing frequency and cost of replacing components.
Smart Images

Figure CN119522144A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for casting a component for use in a high wear industrial environment, the component having a composite zone containing titanium carbide in a matrix material. The composite zone is formed in situ during the casting process of a molten bulk material and is obtained by using a powder composition, the powder composition comprising a reactant powder, which forms titanium carbide in the composite zone and contains titanium and carbon, and a moderator powder, which forms a matrix around the titanium carbide in the composite zone and contains a metal powder. Background Art
[0002] In high wear industrial environments, such as those associated with the metallurgical, mining, cement, recycling, energy, agricultural and offshore sectors, the surfaces of the used components are subject to complex wear processes due to the physical phenomena occurring during the activities. These phenomena include, but are not limited to, crushing, fragmenting, milling, drilling, boring, loading and locomotion of solids, liquids and / or their mixtures. These wear processes, including abrasion, erosion, adhesion, surface fatigue and / or tribo-corrosion, can lead to a reduction in component size and ultimately to a loss of functionality and degradation of the performance of specific structural components. This necessitates the frequent replacement of these components, which increases costs and reduces the profitability of the machines and processing routes used.
[0003] It is well known that in order to extend the service life of components used in high wear applications, the periphery of the component exposed to wear conditions and the internal body materials constituting the main dimensions of the component must have high hardness and high plasticity respectively. This ensures a certain degree of wear resistance while avoiding complete embrittlement and / or catastrophic failure of the component.
[0004] Therefore, usually, finished components, that is, components that have been formed and have reached or are close to the final product size, are coated with hard coatings on their surfaces by spraying, cladding, welding, electroplating and other technologies before being put into use. These layers usually contain a high content of ceramic phases, such as carbides, borides and / or nitrides, which are distributed in a matrix material, which is usually composed of a metallic material. Since the wear-resistant coating is applied after the component is formed, there will be problems with bonding with the underlying main material and incomplete coverage due to the peculiarities of grooves and other shapes. In addition, the manufacture of such components requires multiple processes, which increases production time and related costs.
[0005] As an alternative to applying a hard coating after molding, the harder peripheral regions of the component can be produced in situ during the initial casting of the molten host material, thereby reducing the number of manufacturing steps required for the component.
[0006] WO 2017 / 081665 A1 discloses a casting having a composite zone containing titanium carbide. A casting insert is formed using a mixed powder containing 100wt.%, 90wt.%, 70wt.%, 50wt.%, 30wt.% and 10wt.% reaction powder and 0, 10wt.%, 30wt.%, 50wt.%, 70wt.% and 90wt.% adjustment powder, respectively. The reaction powder consists of 50 atomic % Ti and 50 atomic % C, and the adjustment powder is high manganese steel. The insert is then placed and fixed on the wall of the casting mold cavity. Six kilograms of molten cast steel are poured into the mold, and heat energy is provided by the molten cast steel to induce a reaction between titanium and carbon. A composite zone containing titanium carbide is formed in a matrix composed of high manganese steel by a self-propagating high temperature synthesis (SHS) reaction, thereby generating a harder area of the component where the powder composition (in the form of a casting insert) was originally placed. The main dimensions of the casting are composed of cast steel.
[0007] However, WO 2017 / 081665 A1 further discloses that for castings made with very small amounts of adjusting powder (i.e., 0wt.%, 10wt.%, and 30wt.%), no stable composite zone is obtained. On the contrary, the titanium carbide fragments in the high manganese steel matrix are randomly distributed throughout the main dimensions of the casting and do not stay in the target position. This prevents the local strengthening of the hardness value in the casting area exposed to severe wear conditions. In addition, due to the random distribution of titanium carbide phases, they cannot form an interconnected network, thereby reducing the crack resistance of the component and promoting local collapse. Therefore, it is necessary to increase the adjusting powder to at least 50wt.% to establish a more stable composite zone. However, this also correspondingly reduces the amount of reactive powder that can be used and the amount of titanium carbide phase formed therewith. Since titanium carbide plays a major role in the hardness of the composite zone, reducing the amount of titanium carbide to ensure the stability of the composite zone can achieve maximum hardness of the casting. Summary of the invention
[0008] The present invention therefore aims to propose a method for casting a component having improved hardness characteristics in the composite zone of the component thus cast.
[0009] The present invention proposes a method for casting a component for use in a high-wear industrial environment, wherein the component has a composite zone containing titanium carbide in a matrix material, wherein the composite zone is formed in situ during the casting process of a molten main body material and is obtained by using a powder composition, wherein the powder composition comprises a reaction powder and a regulating powder, wherein the reaction powder forms titanium carbide in the composite zone and comprises titanium and carbon, and the regulating powder forms a matrix surrounding the titanium carbide in the composite zone and comprises a metal powder, characterized in that the powder composition consisting of 55-80wt.% of the reaction powder and 20-45wt.% of the regulating powder is inserted into a mold cavity having a wall thickness of at least 40mm, and at least 30kg, preferably at least 100kg, of molten main body material is poured into the mold cavity.
[0010] The composite zone of the casting is formed in situ during the casting process of the molten main material. This is due to the known self-propagating high temperature synthesis (SHS) reaction, which begins when the molten main material reaches the powder composition contained in the mold cavity. The powder composition contains elements and / or compounds that form the phases of the resulting composite zone. In addition, the powder composition contains reaction powder and adjustment powder, which form the reinforcement phase and the surrounding matrix, respectively. The powder composition consists of 55-80wt.% reaction powder and 20-45wt.% adjustment powder. The reaction powder consists of 45 atomic% Ti:55 atomic% C or 55 atomic% Ti:45 atomic% C powder with a certainty of 2%. Preferably, the titanium powder comes from a pure metal and contains only impurities related to the manufacturing and / or comminution process. Most preferably, the titanium powder contains at least 95.5 atomic% Ti, a maximum of 0.03 atomic% H and a maximum of 0.4 atomic% O. The particle size of the titanium powder does not exceed 70 μm, but preferably does not exceed 50 μm, more preferably does not exceed 40 μm, and most preferably 35 μm. The titanium powder is preferably an irregular sponge powder, usually manufactured by a hydrogenation-dehydrogenation process. The carbon powder is preferably graphite, flake graphite, amorphous graphite, black carbon, a carbonaceous material or a mixture thereof. Preferably, the carbon powder contains at least 96.1 atomic % C and at most 0.05 atomic % S. The particle size of the carbon powder is at most 20 μm, but preferably does not exceed 10 μm, more preferably does not exceed 5 μm, and most preferably is between 5-10 μm.
[0011] The regulating powder may include at least one powdered metal from Fe, Co, Ni, Mo, Cr, W, Al, Mn, Cu, Si, Ti, V, B, Li or Mg, preferably including at least two of these metals. Preferably, the regulating powder includes a mixture containing Fe, Mn, Si and C powders, and most preferably also includes Cr powder. The maximum content of H in the regulating powder is preferably 0.03 atomic%. Preferably, the chemical composition of the regulating powder is related to gray cast iron, white cast iron, chromium cast iron, chromium cast steel, non-alloy cast steel, low alloy cast steel, martensitic cast steel, stainless steel cast steel, heat-resistant cast steel, manganese cast steel or Ni-Cr cast iron. Due to its influence on compactness, the shape of the regulating powder is preferably irregular. In addition, in the case where Fe is the main component of the regulating powder, the powder particle size distribution of iron is preferably between 45 μm and 150 μm. If the main component of the regulating powder is Cr, the powder particle size is preferably 63 μm.
[0012] For example, the powder composition is inserted into the die cavity in the form of a compacted insert and / or coating. The powder composition can be inserted and positioned so that it directly contacts the die cavity wall, which surrounds the cavity of the mold. The powder composition can also be inserted and positioned so that a distance is maintained between the powder composition and the wall of the die cavity. Preferably, the distance between the powder composition and the die cavity wall does not exceed 20 mm, and preferably at least 5 mm is maintained. By ensuring the distance between the powder composition in the form of a compacted insert and the die cavity, the heat energy consumption of the die material from the SHS reaction front during the carbide formation process can be prevented and / or reduced. In addition, the powder composition is placed in an area of the die cavity associated with the casting area that needs to be reinforced. Those skilled in the art know how to make inserts and / or coatings.
[0013] The positioning of the casting insert in the mold cavity can be achieved by an assembly system, which can include elements such as wires, perforated metal sheets, screws, nuts, washers, etc. Then, various ring and track systems are made using these components, for example, the individual casting inserts are threaded together by wires or metal rods to ensure the fixed position of the inserts. Subsequently, the casting inserts are fixed by metal bolts and / or screws, etc. to ensure that the determined position is maintained during the insertion process.
[0014] When constructing the assembly system used, care must be taken when positioning and placing the individual casting inserts to ensure that there is an appropriate distance between them. Due to the high permeability, the size of the inserts may increase after the in-situ SHS reaction, thereby affecting the fusion of the individual composite zones. This can further lead to the initiation and propagation of cracks during solidification and post-casting heat treatment. To avoid this destructive phenomenon, a minimum spacing of 5 mm, preferably 8 mm, must be maintained between the casting inserts. In addition, the spacing should be increased to 10 mm, preferably 12 mm after every 4, preferably 8 casting inserts. The spacing between casting inserts should not exceed 30 mm, preferably 25 mm.
[0015] Once the molten host material is poured into the mold and reaches the powder composition, the synthesis reaction is initiated by spot heating the powder. The thermal energy of the liquid host material provides the activation energy for igniting the synthesis reaction between titanium and carbon. Titanium carbide begins to form. This synthesis reaction is a highly exothermic combustion reaction, and the heat and combustion wave generated travel through the powder composition, converting the reaction powder into titanium carbide product. Therefore, the reaction is self-sustaining and continues until the powder composition is completely reacted and / or the heat dissipation rate of the reaction front exceeds the heat generation rate of the reaction front. Once the titanium carbide phases begin to form, they will continue to nucleate, grow and eventually aggregate together.
[0016] However, the high enthalpy of formation of titanium carbide (-183 kJ / mol) is equivalent to the highly exothermic nature of the formation reaction, resulting in a rapid increase in the temperature of the reaction front. These high temperatures promote the penetration of the molten main material between the individual titanium carbide phases. This is due to, for example, the decrease in viscosity when the temperature increases, which promotes the flow of the molten main material between the titanium carbide phases, eventually separating them and possibly transporting them from the predetermined position in the cavity mold to the inner main dimensions of the casting. This phenomenon of separation of titanium carbide by the molten main material is called destructive penetration, while the distribution of titanium carbide away from the composite zone is called destructive crushing. Both phenomena are detrimental to the service life of the casting. Not only is it expected that the mechanical properties of the composite zone (such as hardness) will be reduced, but the hard and brittle titanium carbide phase contained throughout the component will also lead to crack propagation and reduce the fracture toughness and durability of the casting.
[0017] Furthermore, the heat released by the reaction and the associated temperature rise can be dissipated into the surroundings, leading to the evaporation of volatile components and the decomposition of the resulting products. The release and dissolution of these gaseous products leads to an imminent risk of the formation of voids and pores within the intended composite zone. This further reduces the hardness and wear resistance values, while also reducing the flexural strength of the component.
[0018] The conditioning powder component in the powder composition can absorb and dissipate the high heat energy generated by titanium carbide in the SHS reaction by melting. This reduces the penetration of the molten main material between the carbides and hinders the destructive crushing of the composite zone. Therefore, the conditioning powder plays a core role in stabilizing the composite zone. In addition, since the conditioning powder will eventually form a matrix material embedded in the titanium carbide phase, the mechanical properties of the matrix and the selected conditioning powder will affect the mechanical properties of the resulting composite zone.
[0019] The ratio of reactive powder to conditioning powder in the powder composition determines the stability and hardness value of the resulting composite zone. If the amount of conditioning powder is insufficient, destructive crushing will occur and the local target mechanical properties will not be achieved. However, if the amount of conditioning powder exceeds the stability requirements, the hardness value cannot be maximized due to the low titanium carbide content. Therefore, the amount of conditioning powder must be reduced as much as possible to maintain the integrity of the composite zone while maximizing the titanium carbide content and its associated hardness value.
[0020] According to the invention, the optimal ratio between the reaction powder and the conditioning powder is not an independent variable, but is directly influenced by the casting parameters during the manufacture of the cast component. In particular, the destructive penetration and crushing phenomena of the composite zone can be controlled by changing the geometry of the mold cavity. According to the invention, the amount of conditioning powder required to stabilize the composite zone can be reduced by enlarging the size of the mold cavity and the resulting casting. This ensures that more titanium carbide phases are produced, thereby increasing the overall hardness of the composite zone.
[0021] The two main aspects that characterize the geometry of a mold cavity are the overall volume of the cavity and the specific dimensions, or shape, of the cavity.
[0022] The total volume of the mold cavity is usually represented by the weight of the molten host material poured into the mold cavity. The relationship between these parameters is determined by the density of the host material. However, since the mold cavity already contains the powder composition before the molten host material is cast, the effective mold cavity volume can be calculated by subtracting the volume of the powder composition inserted into the mold cavity from the total volume of the mold cavity, which volume reflects the amount of molten host material to be cast. However, the volume only quantifies the three-dimensional space enclosed by the surface. Therefore, it alone cannot provide sufficient information about the solidification process of the molten host material, because the distribution of this volume within the mold cavity is also important.
[0023] Due to the specific shape or size of the mold cavity, the molten body material will have a volume distribution within the mold cavity. Due to the shape of the casting, this may result in different local volumes throughout the mold cavity. The smallest of the three dimensions that define the local volume is called the wall thickness. Local volumes with smaller wall thickness values cool faster and solidify more quickly. In contrast, local volumes with thicker walls cool slower and solidify more slowly. This is due to the combined effects of the associated heat transfer processes and paths, as well as the thermal conductivity and heat capacity properties of the molten body material and / or the mold material.
[0024] According to the present invention, the local volume of interest is the area of the mold cavity containing the powder composition. Therefore, the wall thickness according to the present invention is related to the minimum of the three dimensions defining the local volume within the mold cavity containing the powder composition. It will be understood that the mold cavity can have various wall thickness values, but preferably has only a single wall thickness value.
[0025] It can also be speculated that because the specific shape of the mold cavity determines the distribution of the molten bulk material, other processes such as diffusion are also affected and constrained by the size of the mold cavity. For example, various transport phenomena related to diffusion are restricted by the walls of the mold cavity and are therefore directed and / or hindered. Therefore, the total thickness of the mold cavity wall (i.e., the wall thickness) allows for the expansion of the diffusion path with increasing size, but does not provide the same amount of accommodation as a smaller wall thickness.
[0026] The volume of the mold cavity (expressed in terms of the weight of the molten host material to be cast) and the mold cavity dimensions (more specifically the wall thickness) together influence the occurrence of destructive penetration and crushing. The synergistic relationship between wall thickness and total cast weight provides a method for predicting which mold cavity geometries will inherently result in a reduction in the necessary conditioning powder to stabilize the resulting composite regions. Thus, according to the present invention, casting at least 30 kg, preferably at least 100 kg, of molten host material into a mold cavity having a wall thickness of at least 40 mm requires the use of a powder composition consisting of 55-80 wt.% of reactive powder and 20-45 wt.% of conditioning powder to produce a casting having composite regions.
[0027] According to a preferred embodiment of the present invention, when pouring at least 100 kg of molten main body material into a mold cavity having a wall thickness of at least 80 mm, a powder composition consisting of 60-80 wt.% of reaction powder and 20-40 wt.% of adjustment powder should be inserted into the mold cavity. In this case, the molten main body material can be manganese steel or martensitic steel.
[0028] According to another preferred embodiment of the present invention, when pouring at least 250 kg of molten main body material into a mold cavity having a wall thickness of at least 80 mm, a powder composition consisting of 70-80 wt.% of reaction powder and 20-30 wt.% of adjustment powder should be inserted into the mold cavity. In this case, the molten main body material can be manganese steel or martensitic steel.
[0029] According to another preferred embodiment of the present invention, when pouring at least 600 kg of molten main material into a mold cavity having a wall thickness of at least 85 mm, a powder composition consisting of 60-80 wt.% of reaction powder and 20-40 wt.% of adjustment powder should be inserted into the mold cavity. In this case, the molten main material can be cast iron, gray cast iron or white chrome cast iron.
[0030] According to another preferred embodiment of the present invention, when pouring at least 800 kg of molten main body material into a mold cavity having a wall thickness of at least 50 mm, a powder composition consisting of 55-70 wt.% of reaction powder and 30-45 wt.% of adjustment powder should be inserted into the mold cavity. In this case, the molten main body material can be manganese steel or martensitic steel.
[0031] In addition, the present invention also proposes a casting for use in a high-wear industrial environment, wherein the casting has a composite zone containing titanium carbide in a matrix material, wherein the composite zone is formed in situ during the casting process of the molten main material and is obtained by using a powder composition, wherein the powder composition comprises a reaction powder and an adjustment powder, wherein the reaction powder forms titanium carbide in the composite zone and comprises titanium and carbon, and the adjustment powder forms a matrix surrounding the titanium carbide in the composite zone and comprises metal powder, wherein the main material weight of the casting is at least 30 kg, preferably at least 100 kg, and the wall thickness of the casting is at least 40 mm.
[0032] The casting comprises a bulk material constituting the major dimensions of the part and a composite region located at the periphery of the part. The periphery refers to the outer surface of the part in direct contact with the surrounding environment and / or a near-surface region located below the outer surface of the part but not necessarily in contact with the outer surface. Preferably, the near-surface region is spaced apart from the major dimensions of the part and is surrounded by the cast bulk material.
[0033] The main material is a metallic material based on iron, nickel or cobalt. Preferably, the main material is an iron alloy containing carbon, chromium, manganese and / or silicon. Most preferably, the main material is non-alloy cast steel, low alloy cast steel, manganese cast steel, martensitic cast steel, cast iron, gray cast iron or white chrome cast iron. It is understood that impurities associated with the production of the main material (whether pure metal or industrial alloy) should not be taken into account because these impurities are not intentionally added and it is not economically feasible to remove them. These impurities are generally referred to as accidental impurities and may include sulfides, oxides and nitrides, such as MnS, Al2O3, TiN, and / or elements such as S, P, Ti, Al and / or Ca.
[0034] A composite region is a region of a component that contains at least one phase that differs in chemical and / or physical properties from the main material and does not originate from the main material. In addition, this phase also differs in chemical and / or physical properties from the matrix material surrounding it. A composite region according to the invention contains at least titanium carbide, preferably only titanium carbide, as a ceramic phase.
[0035] The matrix material and the main body material are preferably not the same material. The matrix material is preferably a metallic material and comprises at least one metal from Fe, Co, Ni, Mo, Cr, W, Al, Mn or Cu, preferably at least two of these metals. Preferably, the matrix material comprises Fe, Mn, Si and C, and most preferably further comprises Cr powder. Most preferably, the matrix material has a chemical composition related to gray cast iron, white cast iron, chromium cast iron, chromium cast steel, non-alloy cast steel, low alloy cast steel, manganese cast steel or Ni-Cr cast iron.
[0036] Preferably, the titanium carbide content in the composite zone is at least 40 volume %, preferably at least 50 volume %, more preferably at least 60 volume %, and most preferably at least 70 volume %. The remaining volume in the composite zone comprises matrix material. It is understood that the composite zone may also contain a main body material. Preferably, the amount of main body material is less than 60 volume %, more preferably less than 40 volume %, still more preferably less than 20 volume %, and most preferably less than 10 volume %. The boundary between the composite zone and the main dimension of the casting is defined by the amount of titanium carbide less than 40 volume %.
[0037] The composite zone presents spherical titanium carbide phases, which are preferably agglomerated together to form a scaffold or spider web that can be regarded as a titanium carbide phase. It is understood that the scaffold can also be composed of individual titanium carbide phases that are aggregated together so that they are directly adjacent to each other, but are still separate phases. This scaffold connects the individual titanium carbide phases to each other, and most preferably connects all titanium carbide phases in the composite zone to each other, while the matrix material is located in the gap area formed by the titanium carbide scaffold. This scaffold has a blocking and redirecting effect, which can prevent crack propagation. In addition, by preventing individual titanium carbides from being present in the matrix material, the risk of cracking and fragmentation of the composite zone can be reduced. Therefore, preferably only a small amount, most preferably zero individual titanium carbide phases are present in the matrix material. For example, when imaged using an optical microscope or a scanning electron microscope, the above-mentioned composite zone can be regarded as presenting a lake view or a "foam on water"-like appearance.
[0038] Preferably, the casting as described above is a hammer, a blow bar, a roll, a cone, a bowl, a plate, a screen lining, a tooth, a chute or a pipe.
[0039] According to a preferred embodiment of the present invention, the wall thickness of the casting is at least 80 mm, and the weight of the main body material of manganese steel or martensitic steel is at least 100 kg.
[0040] According to another preferred embodiment of the present invention, the wall thickness of the casting is at least 80 mm, and the weight of the main body material of manganese steel or martensitic steel is at least 250 kg.
[0041] According to another preferred embodiment of the present invention, the wall thickness of the casting is at least 85 mm, and the weight of the cast iron, grey cast iron or white chrome cast iron main body material is at least 600 kg.
[0042] According to another preferred embodiment of the present invention, the wall thickness of the casting is at least 40 mm, and the weight of the main body material of manganese steel or martensitic steel is at least 800 kg. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] The present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings. The corresponding specific embodiments further illustrate the details, features and advantages of the present invention. The following drawings include:
[0044] Figure 1: Schematic diagram of the casting jaw (A), including a perspective view of the casting insert used (B) and a part of the assembly system used (C), as well as the insertion position of the assembly system in the mold cavity (D) and the final position of the composite zone in the casting jaw part (D).
[0045] FIG. 2 : Schematic diagram of a casting bowl (A), a cross-sectional view of the casting bowl wall (B), showing the location of the resulting composite zone, and the assembly system for positioning and inserting the casting inserts (C and D) into the corresponding mold cavities (E).
[0046] Figure 3: Schematic diagram of the casting cone (A), cross-section of the casting cone wall (B), showing the location of the resulting composite zone, and the assembly system for positioning and inserting the casting inserts (C and D) into the corresponding mold cavities (E).
[0047] Figure 4: Schematic diagram of the casting roll (A), cross-section of the casting roll wall (B), showing the location of the resulting composite zone, and rings for building an assembly system for positioning and inserting the casting inserts (C) into the corresponding mold cavities (D).
[0048] Figure 5 : Scanning electron micrographs of the upper composite zone (A to D) of the roller according to Example 4, and the transition area (E) between the composite zone and the main body material, the composite zone being cast using a powder composition comprising 75 wt.% of reaction powder and 25 wt.% of conditioning powder.
[0049] Figure 6: Schematic diagram of a casting blow bar (A), a cross-sectional view of the casting roll wall (B) showing the location of the resulting composite zone, and part of the assembly system for positioning and inserting the casting insert into the mold cavity (C).
[0050] Fig. 7: Scanning electron micrographs (A and B) of the composite zone of a blow hammer according to Example 5, cast using a powder composition comprising 70 wt.% of reaction powder and 30 wt.% of conditioning powder.
[0051] Figure 8: Schematic diagram of a casting hammer (A), a cross-sectional view of the casting hammer wall (B) showing the location of the resulting composite zone, and part of the assembly system for positioning and inserting the casting insert into the mold cavity (C). DETAILED DESCRIPTION
[0052] Example 1
[0053] As described in detail below, this embodiment is intended to produce Figure 1A A jaw crusher jaw component 100 is shown which is reinforced with a titanium carbide composite zone.
[0054] The powder composition is produced by mixing 70wt.% of a reaction powder with 30wt.% of an adjustment powder. The reaction powder comprises a titanium sponge powder and flake graphite, wherein the titanium sponge powder is made by a hydrogenation-dehydrogenation reaction and is composed of at least 99atomic% Ti, a maximum of 0.4atomic% O and 0.03atomic% H, and the flake graphite is composed of at least 96atomic% C and a maximum of 0.05atomic% S. Both the titanium powder and the carbon powder are irregularly shaped, with average diameters of 35μm and 5-10μm, respectively. The ratio of titanium powder to carbon powder is 45atomic%:55atomic% C. The composition of the adjustment powder is manganese steel, containing 21wt.% manganese as well as Fe, Si and C. In addition, since an iron alloy is used to make the adjustment powder, it is not ruled out that it contains a small amount of other elements.
[0055] Subsequently, the powders were mixed, dried, and subjected to uniaxial cold pressing at a compaction pressure of 500 MPa or isostatic pressing at a pressure of 200 MPa to obtain 136 casting inserts 101 with a size of 20×20×100 mm.
[0056] Then, if Figure 1B As shown, two through holes 102 are drilled on the produced casting insert 101 by a conventional drilling method to construct 17 assembly systems 103 for placement in the mold cavity. Figure 1C 1 shows a portion of an assembly system 103, each assembly system 103 consisting of eight casting inserts 101, which are spaced 8 mm apart from each other and fixed to the same perforated metal plate 104 by screws 105. Thus, the assembly system 103 is placed and positioned in a mold cavity 106 of a sand mold, the cross section of which is as shown in FIG. Figure 1D As shown, the most severely worn part of the jaw member 100 is located at the vertex 107 of the jaw teeth. The wall thickness 108 of the vertex 102 connected to the tooth width is 40 mm, and the wall thickness 109 of the vertex 102 connected to the tooth root is 40 mm.
[0057] 800 kg of molten host material consisting of manganese steel with a Mn content of 12 wt.% was poured into the mold cavity. The heat energy of the molten steel triggered a self-propagating high temperature synthesis (SHS) reaction between the titanium and carbon components in the powder composition. The powder melting was regulated to dissipate the generated heat energy and prevent the molten host material from penetrating and causing destructive crushing.
[0058] like Figure 1D As shown in a portion of a cross-sectional view of a cast jaw member 100 in FIG. 1 , the resulting composite region 110 has a spherical titanium carbide phase uniformly distributed in a matrix material comprising a manganese steel containing 21 wt.% Mn as well as Fe, Si and C. The main body material 111 of the jaw member 100 surrounds the composite region 110 and exhibits a softer austenitic microstructure composed of the manganese cast steel.
[0059] The mechanical properties of the composite zone 110 and the main material 111 were measured and the results are shown in Table 1 below. The hardness values were obtained by Vickers hardness testing with a test load of 294.3N and a holding time of 10 seconds. Ten measurements were performed at each test position and the results were averaged. Wear resistance was tested using the ball-on-disc method, i.e. dry sliding wear, according to ISO 20808:2004. The test was performed using an Ebit Polska friction and wear tester using a corundum ball component with a diameter of 3.175mm in the friction pair system. Further test parameters included a friction radius of approximately 3.5mm, a disc speed of 192RPM, a test load of 10N, and a friction path of 704m. After completing the ball-on-disc test, the sample was 3D scanned and the depth measurement of the resulting track cross section was performed to determine the wear index.
[0060] Table 1: Hardness and wear properties of the composite zone and body materials of the jaw components.
[0061]
[0062] As shown in Table 1, the composite region 110 of the jaw member 100 is more than twice as hard as the surrounding body material 111 and is almost 15 times more wear resistant.
[0063] Example 2
[0064] Example 2 relates to Figure 2A The cast bowl component 200 shown is produced in such a way that it has areas reinforced with titanium carbide for use in cone crushers. Figure 2A The corresponding circle in Figure 2B As shown in the cross-sectional view of the bowl body wall 201 , the bowl body 200 is reinforced by three titanium carbide composite zones, namely, an upper composite zone 202 , a lower inner composite zone 203 and a lower outer composite zone 204 located on the inner circumference of the bowl body wall 201 .
[0065] The powder composition of the upper composite zone 202 is formed by mixing 60 wt.% of the reaction powder with 40 wt.% of the adjustment powder. The reaction powder contains sponge titanium powder, which is made by hydrogenation-dehydrogenation reaction and consists of at least 99 atomic % Ti, up to 0.4 atomic % O and 0.03 atomic % H. The reaction powder also contains flake graphite, which consists of at least 99 atomic % C and up to 0.05 atomic % S. Both the titanium powder and the carbon powder are irregular in shape, with average diameters of 35 μm and 5-10 μm, respectively. The ratio of titanium powder to carbon powder is 45 atomic % Ti: 55 atomic % C. The composition of the adjustment powder is manganese steel, containing 21 wt.% Mn as well as Fe, Si and C. In addition, since the adjustment powder is made of an iron alloy, it is not ruled out that it contains a small amount of other elements.
[0066] The powder composition of the lower inner composite zone 203 is prepared by mixing 63 wt.% of the reaction powder with 37 wt.% of the conditioning powder. The composition, size, morphology and production details of the reaction powder and the conditioning powder are the same as the powder composition of the upper composite zone 202 detailed above. The ratio of titanium powder to carbon powder is also 45 atomic % Ti: 55 atomic % C. The composition of the conditioning powder is also manganese steel, containing 21 wt.% Mn as well as Fe, Si and C, and may contain small amounts of other elements due to the selected powder manufacturing method.
[0067] The powder composition of the lower outer composite region 204 is prepared by mixing 60 wt.% of the reaction powder with 40 wt.% of the conditioning powder. The composition, size, morphology and production details of the reaction powder and the conditioning powder are the same as the powder composition of the upper composite region 202 detailed above. The ratio of titanium powder to carbon powder is also 45 atomic % Ti: 55 atomic % C. The composition of the conditioning powder is also manganese steel, containing 21 wt.% Mn, Fe, Si and C, and may contain small amounts of other elements due to the selected powder manufacturing method.
[0068] Subsequently, the three powders were mixed, dried, and subjected to uniaxial cold pressing at a compaction pressure of 500 MPa or isostatic pressing at a pressure of 200 MPa, and finally 371 casting inserts 205 with a size of 20×20×100 mm were obtained. Among these 289 casting inserts, 115 were composed of powders of the upper composite zone 202, 128 were composed of powders of the lower inner composite zone 203, and 128 were composed of powders of the lower outer composite zone 204.
[0069] like Figure 2C As shown, a casting insert 205 is inserted into the mold cavity of a sand mold via an assembly system 206 . Figure 2D An enlarged portion of the assembly system 206 is shown. The assembly system 206 includes three separate rings, namely, an upper ring 207, a lower inner ring 208, and a lower outer ring 209, corresponding to the upper composite zone 202, the lower inner composite zone 203, and the lower outer composite zone 204, respectively. The upper ring 207, the lower inner ring 208, and the lower outer ring 209 are composed of 115, 128, and 128 casting inserts 205, respectively. Each casting insert 205 has two through holes, which are threadedly connected by two rods 210 to form each of the three rings of the assembly system 206. During the process of inserting the casting insert 205 into the rod 210 and positioning it, a spacing distance of 8 mm is maintained between each casting insert 205. In addition, after every 9 casting inserts 205, the spacing distance is increased to 10 mm.
[0070] The constructed assembly system 206 is then inserted into the mold cavity 211 of the sand mold, at the location where the cone crusher is expected to be most severely worn. Figure 2EAs shown, during the process of installing the assembly system 206 into the mold cavity 211, the lower inner ring 208 and the upper ring 207 are placed at a distance of 10 mm from the inner mold cavity wall. In addition, the distance between the lower outer ring 209 and the lower inner ring 208 is 10 mm, which is maintained by a gasket having the same material properties as the rod 220 in the assembly system 206.
[0071] like Figure 2E As shown, the wall thickness 212 of the mold cavity 211 connected to the upper ring 207 and the lower rings 208 and 209 is 90 mm and 80 mm respectively.
[0072] A molten main body material consisting of a manganese steel having a Mn content of 13 wt.% weighing 1005 kg is poured into the mold cavity 211. The heat energy of the molten steel triggers a self-propagating high temperature synthesis (SHS) reaction between the titanium and carbon components in the powder composition. The powder melting is regulated to dissipate the generated heat energy and prevent the molten main body material from penetrating and causing destructive crushing.
[0073] Therefore, if Figure 2B As shown, in an austenitic main body material 212, three composite zones 202, 203 and 204 are produced, each of which contains spherical titanium carbide in a matrix material comprising a manganese steel containing 21 wt.% Mn as well as Fe, Si and C.
[0074] The main body material 213 of the bowl component 200 surrounds the composite regions 202, 203 and 204, which exhibits a relatively soft austenite microstructure composed of manganese cast steel, as shown in Table 2 below. The mechanical properties of the composite regions 202, 203, 204 and the main body material 213 of the bowl component 200 are measured using a test method similar to the test method of the jaw component 100 in Example 1.
[0075] Table 2: Hardness and wear properties of the composite zone and main body materials of the bowl components.
[0076]
[0077]
[0078] Example 3
[0079] The purpose of this implementation is to produce Figure 3A The cone 300 is shown reinforced by a composite zone containing titanium carbide.
[0080] Figure 3B Depicted through Figure 3AThe cross section of the cone wall 301 taken by the circle in FIG. 3 shows that the cone 300 is reinforced by three titanium carbide composite zones, namely, three composite zones on the periphery of the cone wall 301: an upper composite zone 302, a lower inner composite zone 303 and a lower outer composite zone 304.
[0081] The powder composition of the upper composite zone 302 is formed by mixing 60 wt.% of the reaction powder with 40 wt.% of the adjustment powder. The reaction powder contains sponge titanium powder and flake graphite, the sponge titanium powder is made by hydrogenation-dehydrogenation reaction, and is composed of at least 99 atomic % of Ti and a maximum of 0.4 atomic % of O and 0.03 atomic % of H, and the flake graphite is composed of at least 99 atomic % of C and a maximum of 0.05 atomic % of S. Both the titanium powder and the carbon powder are irregular in shape, with average diameters of 35 μm and 5-10 μm, respectively. The ratio of titanium powder to carbon powder is 45 atomic % of Ti: 55 atomic % of C. The composition of the adjustment powder is manganese steel, containing 21 wt.% of Mn as well as Fe, Si and C. In addition, since the adjustment powder is made of iron alloy, it is not ruled out that it contains a small amount of other elements.
[0082] The powder composition of the lower inner composite zone 303 is prepared by mixing 63 wt.% of the reaction powder with 37 wt.% of the conditioning powder. The composition, size, morphology and production details of the reaction powder and the conditioning powder are the same as the powder composition of the upper composite zone 201 detailed above. The ratio of titanium powder to carbon powder is also 45 atomic % Ti: 55 atomic % C. The composition of the conditioning powder is also manganese steel, containing 21 wt.% Mn as well as Fe, Si and C, and may contain small amounts of other elements due to the selected powder manufacturing method.
[0083] The powder composition of the lower composite region 304 is prepared by mixing 60 wt.% of the reaction powder with 40 wt.% of the conditioning powder. The composition, size, morphology and production details of the reaction powder and the conditioning powder are the same as the powder composition of the upper composite region 301 detailed above. The ratio of titanium powder to carbon powder is also 45 atomic % Ti: 55 atomic % C. The composition of the conditioning powder also includes manganese steel, containing 21 wt.% Mn as well as Fe, Si and C, and may contain small amounts of other elements due to the selected powder manufacturing method.
[0084] Subsequently, the three powders were mixed, dried, and subjected to uniaxial cold pressing at a compaction pressure of 500 MPa or isostatic pressing at a pressure of 200 MPa, and finally 289 casting inserts 306 with a size of 20×20×100 mm were obtained. Among the 371 casting inserts, 306 were composed of the powder of the upper composite zone 302, 101 were composed of the powder of the lower inner composite zone 303, and 101 were composed of the powder of the lower outer composite zone 304.
[0085] Subsequently, the casting insert 306 is provided with through holes for constructing an assembly system 307 to ensure that the casting insert 306 is inserted and positioned in the sand mold. Figure 3C and 3D As shown, the assembly system 307 includes three separate rings, namely, an upper ring 308, a lower inner ring 309, and a lower outer ring 310, corresponding to the upper composite zone 302, the lower inner composite zone 303, and the lower outer composite zone 304, respectively. The casting inserts 306 of each separate ring are respectively screwed by two rods 311 to construct the corresponding ring of the assembly system 307. During the screwing and positioning of the casting inserts 306 on the rods 311, a spacing distance of 8 mm is maintained between each casting insert 306. In addition, after every 9 casting inserts 306, the spacing distance is increased to 10 mm. Figure 3C and 3D A pattern of spacing distances between the inserts 306 is shown. In addition, the two lower rings 309 and 310 of the assembly system 307 are separated by spacers having the same dimensions and material properties as the rod 311 to which the cast insert 306 is threaded.
[0086] The constructed assembly system 307 is then inserted into the mold cavity 312 of the sand mold, at the location where the cone wear is expected to be most severe. Figure 3E As shown, during the installation of the assembly system 307 into the mold cavity 312, the three rings are placed at a distance of 10 mm from the mold cavity wall. The mold cavity wall thickness 313 connected to the upper ring 308 and the lower ring 309 is 70 mm and 95 mm respectively.
[0087] 840 kg of molten main body material consisting of manganese steel having a Mn content of 13 wt.% is poured into the mold cavity 312. The heat energy of the molten steel triggers a self-propagating high temperature synthesis (SHS) reaction between the titanium and carbon components in the powder composition. The powder melting is regulated to dissipate the generated heat energy and prevent the molten main body material from penetrating and causing destructive crushing.
[0088] Therefore, if Figure 3B As shown, in the austenitic main body material 314, three composite zones 302, 303 and 304 are produced, each of which contains titanium carbide in a matrix material comprising a manganese steel containing 21 wt.% Mn as well as Fe, Si and C. This results in the area of the cone 300 where the powder composition was originally placed becoming harder.
[0089] The bulk material 314 of the cone component 300 surrounds the composite zones 302, 303, and 304, which exhibit a relatively soft austenitic microstructure composed of manganese cast steel, as shown in Table 3 below. The mechanical properties of the composite zones 302, 303, 304 and the bulk material 314 of the bowl assembly 300 were measured using a test method similar to the test method of the jaw component 100 in Example 1.
[0090] Table 3: Hardness and wear properties of the composite zone and main body materials of the cone component.
[0091]
[0092] Example 4
[0093] The production process of the casting roll 400 shown in Figure A is described in detail below. The cross section of the roll wall 401 (taken from Figure 4A The cross-section circle in Figure 4B ) shows that the casting roll 400 has two composite zones containing titanium carbide, namely, an upper composite zone 402 and a lower composite zone 403.
[0094] The powder composition of the upper composite zone 402 is made by mixing 75wt.% of the reaction powder with 25wt.% of the adjustment powder. The reaction powder comprises a titanium sponge powder and flake graphite, the titanium sponge powder is made by hydrogenation-dehydrogenation reaction, and is composed of at least 99atomic% Ti and at most 0.4atomic% O and 0.03atomic% H, and the flake graphite is composed of at least 99atomic% C and at most 0.05atomic% S. Both the titanium powder and the carbon powder are irregular in shape, and the average diameters are 35μm and 5-10μm, respectively. The ratio of titanium powder to carbon powder is 45atomic% Ti: 55atomic% C. The composition of the adjustment powder is high chromium cast iron, containing 16.0wt.% Cr, 3.0wt.% C, 0.6wt.% Si, 0.7wt.% Mn, 0.2wt.% Ni, 2.0wt.% Mo, and the rest is Fe. Furthermore, since the adjustment powder is made of an iron alloy, it is not excluded that a small amount of other elements is contained therein.
[0095] The powder composition of the lower composite region 403 is prepared by mixing 75 wt.% of the reaction powder with 25 wt.% of the conditioning powder. The composition, size, morphology and production details of the reaction powder and the conditioning powder are the same as the powder composition of the upper composite region 201 detailed above. The ratio of titanium powder to carbon powder is also 45 atomic % Ti: 55 atomic % C. The composition of the conditioning powder is also manganese steel, containing 21 wt.% Mn as well as Fe, Si and C, and may contain small amounts of other elements due to the selected powder manufacturing method.
[0096] Subsequently, the two powders are mixed, dried, and subjected to uniaxial cold pressing at a compaction pressure of 500 MPa or isostatic pressing at a pressure of 200 MPa, and finally 289 casting inserts 404 with a size of 15×20×100 mm are obtained. Among these 238 casting inserts, 120 are composed of the powder of the upper composite area 402, and 118 are composed of the powder of the lower composite area 403.
[0097] Using the produced casting insert 404, an assembly system 4 is formed comprising two independent rings 405, an example of which is shown in FIG. Figure 4C As shown. The construction of the assembly system is similar to the construction of the assembly systems 206, 307 described above for the bowl 200 and cone 300 components. Thus, the two rings 405 are connected to the upper composite zone 402 and the lower composite zone 403 formed during the casting process of the casting roll 400. In addition, during the threading and positioning of the individual casting inserts 404, a spacing distance of 8 mm is maintained between each casting insert, and the spacing distance is increased to 10 mm after every 9 casting inserts. Figure 4C A pattern of spacing distances between casting inserts 404 is shown.
[0098] The assembly system is then inserted into the mold cavity 406 of the sand mold, at the location of the expected highest wear on the casting roll 400; see Figure 4D During the installation of the assembly system into the mold cavity 406, both rings 405 are fixed to the mold cavity wall so that the casting insert 404 of each ring 405 is in direct contact with the mold cavity wall. The wall thickness 407 of the mold cavity 406 connected to the upper and lower rings 405 is 60 mm and 70 mm respectively.
[0099] Finally, 850 kg of molten host material consisting of chromium cast iron with a Cr content of 15 wt.% is poured into the mold cavity 406. The heat energy of the molten steel triggers a self-propagating high temperature synthesis (SHS) reaction between the titanium and carbon components in the powder composition. The powder melting is regulated to dissipate the generated heat energy and prevent the molten host material from penetrating and causing destructive crushing.
[0100] Thus, two composite zones 402, 403 are produced, each of which contains a titanium carbide phase in a high chromium cast iron matrix material and a titanium carbide phase in a manganese steel matrix material containing 21wt.% Mn. In addition, partial areas of the two composite zones 402, 403 are surrounded by chromium cast iron containing 15wt.% Cr, which constitutes the main material of the casting roll 400 component.
[0101] Figure 5 A micrograph of the microstructure of the upper composite zone 402 of the casting roll 400 obtained by scanning electron microscopy (SEM) is shown. The titanium carbide phase (labeled as "TiC") is spherical and exhibits a strong network skeleton due to their local aggregation in the matrix phase. In addition, the matrix material (i.e., high chromium cast iron) forms a separate "lake-like" structure that does not contain a separate titanium carbide phase but is surrounded by the TiC carbide network. In addition, Figure 5 E shows the transition region between the composite zone and the chromium cast iron host material.
[0102] The mechanical properties of the composite zones 402, 403 and the bulk material of the casting roll component 400 are measured in a similar manner to the testing method of the jaw component 100 in Example 1.
[0103] Table 4: Hardness and wear properties of composite zone and bulk materials of casting roll components.
[0104]
[0105] Example 5
[0106] like Fig. 6A As shown, the purpose of this embodiment is to produce a plate hammer 500, which is reinforced by a titanium carbide composite area 501 (such as Figure 6B shown). Figure 6B is along Fig. 6A A cross-sectional view of the blow hammer 500 taken along the section line X_X in FIG. 1 shows two rows of composite zones 501 parallel to the length of the blow hammer 500 .
[0107] A powder composition is produced by mixing 70wt.% of a reaction powder with 30wt.% of an adjustment powder. The reaction powder comprises a titanium sponge powder and flake graphite, wherein the titanium sponge powder is made by a hydrogenation-dehydrogenation reaction and is composed of at least 99atomic% Ti, a maximum of 0.4atomic% O and 0.03atomic% H, and the flake graphite is composed of at least 96atomic% C and a maximum of 0.05atomic% S. Both the titanium powder and the carbon powder are irregularly shaped, with average diameters of 35μm and 5-10μm, respectively. The ratio of titanium powder to carbon powder is 45atomic%:55atomic% C. The composition of the adjustment powder is a martensitic cast steel containing 4.5wt.% Cr as well as Fe, Mn, Si and C. In addition, since an iron alloy is used to make the adjustment powder, it is not ruled out that a small amount of other elements is contained therein.
[0108] Subsequently, the powders were mixed, dried, and subjected to uniaxial cold pressing at a compaction pressure of 500 MPa or isostatic pressing at a pressure of 200 MPa to obtain 80 casting inserts 502 with dimensions of 18×20×100 mm.
[0109] Then, if Figure 6CAs shown, these casting inserts 502 are inserted into the mold cavity of the sand mold through an assembly system 503. The assembly system 503 includes two rows of inserts 502, which are placed at the top and bottom of a guide rail 504 and fixed to the guide rail by screws 505, which are inserted into two through holes of each casting insert 502. When positioning the casting inserts 502, a spacing distance of 8 mm is maintained between them. Each row of casting inserts contains 20 individual casting inserts 502. The assembly system 503 is then inserted into the mold cavity, 10 mm away from the mold cavity wall. The wall thickness at the position is 80 mm. A molten main body material consisting of a martensitic cast steel with a Cr content of 3 wt.% is poured into the mold cavity with a weight of 280 kg. The thermal energy of the molten steel triggers a self-propagating high temperature synthesis (SHS) reaction between the titanium and carbon components in the powder composition. The powder melting is regulated to dissipate the generated heat energy to prevent the molten main body material from penetrating and causing subsequent destructive crushing.
[0110] Therefore, as shown in the scanning electron micrograph of Figure 7, a composite region 501 containing a titanium carbide phase (TiC) is formed in the martensitic cast steel matrix material. Due to the agglomeration, the titanium carbide phase is spherical and presents a network skeleton, and the martensitic cast steel matrix material forms a separate "lake-like" structure therein. As shown in the figure, these structures rarely contain a separate titanium carbide phase, but are surrounded by a titanium carbide network skeleton.
[0111] In addition, as shown in the mechanical property values in the table, the hardness and wear resistance of the plate hammer 500 region including the composite zone 501 are higher than those of the surrounding martensitic main material. The measurement method of the above mechanical properties is similar to the test method of the jaw member 100 in Example 1.
[0112] Table 5: Hardness and wear properties of the composite zone and main body material of the blow bar component.
[0113]
[0114] Example 6
[0115] The purpose of this embodiment is to produce a hammer 600 that is reinforced by a composite zone containing titanium carbide. Fig. 8A The section line XX in Figure 8B As shown, hammer 600 has four composite areas 601 at its lower corners, with two composite areas 601 at each corner, perpendicular to each other.
[0116] A powder composition is produced by mixing 65wt.% of a reaction powder with 35wt.% of an adjustment powder. The reaction powder comprises a titanium sponge powder and flake graphite, wherein the titanium sponge powder is made by a hydrogenation-dehydrogenation reaction and is composed of at least 99atomic% Ti, a maximum of 0.4atomic% O and 0.03atomic% H, and the flake graphite is composed of at least 96atomic% C and a maximum of 0.05atomic% S. Both the titanium powder and the carbon powder are irregularly shaped, with average diameters of 35μm and 5-10μm, respectively. The ratio of titanium powder to carbon powder is 45atomic%:55atomic% C. The composition of the adjustment powder is a martensitic cast steel containing 10wt.% Cr as well as Fe, Mn, Si and C. In addition, since an iron alloy is used to make the adjustment powder, it is not ruled out that a small amount of other elements is contained therein.
[0117] Subsequently, the powders were mixed, dried, and subjected to uniaxial cold pressing at a compaction pressure of 500 MPa or isostatic pressing at a pressure of 200 MPa to obtain 36 casting inserts 602 with dimensions of 30×20×100 mm.
[0118] Before being inserted into the mold cavity of the sand mold, each casting insert 602 with two through holes is screwed together by screws 605 and fixed to a perforated metal plate 604, such as Figure 8C , which shows a portion of the assembly system. During the positioning process, a spacing distance of 8 mm is maintained between the casting inserts 602, and this distance is increased to 10 mm after every 4 casting inserts 602. The constructed assembly system 603 is then placed in the sand mold, at a location where the highest wear is expected, 5 mm from the mold cavity wall. The wall thickness at this location is 80 mm.
[0119] A molten main body material consisting of a martensitic cast steel having a Cr content of 10 wt.% weighing 100 kg is poured into the mold cavity. The thermal energy of the molten steel triggers a self-propagating high temperature synthesis (SHS) reaction between the titanium and carbon components in the powder composition. The powder melting is regulated to dissipate the generated heat energy to prevent the molten main body material from penetrating and causing subsequent destructive crushing. Thus, a composite zone 601 is manufactured, which comprises titanium carbide in a matrix material, the matrix material comprising a martensitic cast steel having 10 wt.% Cr as well as Fe, Mn, Si and C. As shown in the mechanical properties listed in Table 6 below, this makes the area of the hammer component 600 harder and more wear-resistant than the martensitic main material. The measurement method of these mechanical properties is similar to the test method described in Example 1 for the jaw component 100.
[0120] Table 6: Hardness and wear properties of the composite zone and main body materials of the hammer components.
[0121]
[0122] Reference Number List
[0123] 100 Jaw
[0124] 101 Casting Insert
[0125] 102 Through Hole
[0126] 103 Assembly system
[0127] 104 Metal Plate
[0128] 105 Screws
[0129] 106 Cavity
[0130] 107 Vertex
[0131] 108 Wall thickness
[0132] 109 Wall thickness
[0133] Multiple District 101
[0134] 111 Main material
[0135] 200 bowl
[0136] 201 bowl wall
[0137] 202 Upper Composite District
[0138] 203 Lower Inner Complex
[0139] 204 Xiawai Complex
[0140] 205 Casting Insert
[0141] 206 Assembly System
[0142] 207 Sheung Wan
[0143] 208 Lower Inner Ring
[0144] 209 Lower Outer Ring
[0145] 210 bars
[0146] 211 Cavity
[0147] 212 Wall thickness
[0148] 213 Main material
[0149] 300 vertebrae
[0150] 301 Vertebral wall
[0151] 302 Upper Composite District
[0152] 303 Lower Inner Complex
[0153] 304 Xiawai Complex
[0154] 305 Vertebral wall
[0155] 306 Casting Insert
[0156] 307 Assembly System
[0157] 308 Sheung Wan
[0158] 309 Lower Inner Ring
[0159] 310 Lower Outer Ring
[0160] 311 bars
[0161] 312 Cavity
[0162] 313 Wall Thickness
[0163] 314 Main material
[0164] 400 Casting Roller
[0165] 401 Casting roller wall
[0166] 402 Upper Multiple District
[0167] 403 Lower Multiple District
[0168] 404 Casting Insert
[0169] 405 Ring
[0170] 406 Cavity
[0171] 407 Wall Thickness
[0172] 500 Blow Hammer
[0173] Multiple District 501
[0174] 502 Casting Insert
[0175] 503 Assembly System
[0176] 504 Guide Rail
[0177] 505 Screws
[0178] 600 Hammer
[0179] Multiple District 601
[0180] 602 Casting Insert
[0181] 603 Assembly System
[0182] 604 Metal Plate
[0183] 605 Screws
Claims
1. A method for casting a component for use in a high wear industrial environment, the component having a composite zone containing titanium carbide in a matrix material, the composite zone being formed in situ during the casting process of a molten host material and being obtained by using a powder composition, the powder composition comprising a reaction powder and a conditioning powder, the reaction powder forming titanium carbide in the composite zone and comprising titanium and carbon, the conditioning powder forming a matrix around the titanium carbide in the composite zone and comprising a metal powder, characterized in that A powder composition consisting of 55-80 wt.% reaction powder and 20-45 wt.% conditioning powder is inserted into a mold cavity having a wall thickness of at least 40 mm, and at least 30 kg, preferably at least 100 kg, of molten host material is poured into the mold cavity.
2. The method for casting a component according to claim 1, characterized in that A powder composition consisting of 60-80 wt.% of reaction powder and 20-40 wt.% of adjustment powder is inserted into a mold cavity having a wall thickness of at least 80 mm, and at least 100 kg of molten host material is poured into the mold cavity, the molten host material being manganese cast steel or martensitic cast steel.
3. The method of casting a component according to claim 1, characterized in that A powder composition consisting of 70-80 wt.% reaction powder and 20-30 wt.% adjustment powder is inserted into a mold cavity having a wall thickness of at least 80 mm, and at least 250 kg of molten host material is poured into the mold cavity, the molten host material being manganese cast steel or martensitic cast steel.
4. The method of casting a component according to claim 1, characterized in that A powder composition consisting of 60-80 wt.% of reaction powder and 20-40 wt.% of adjusting powder is inserted into a mold cavity with a wall thickness of at least 85 mm, and at least 600 kg of molten host material is poured into the mold cavity, the molten host material being cast iron, gray cast iron or white chrome cast iron.
5. The method of casting a component according to claim 1, characterized in that A powder composition consisting of 55-70 wt.% reaction powder and 30-45 wt.% adjustment powder is inserted into a mold cavity with a wall thickness of at least 50 mm, and at least 800 kg of molten host material is poured into the mold cavity, the molten host material being manganese cast steel or martensitic cast steel.
6. Method for casting a component according to any one of the preceding claims, characterized in that The powder composition is inserted into the mold cavity as a layer and / or at least one casting insert.
7. Method for casting a component according to any one of the preceding claims, characterized in that The powder composition is inserted into the mold cavity as at least two casting inserts, the spacing between the casting inserts being at least 5 mm, preferably at least 8 mm.
8. The method of casting a component according to claim 7, characterized in that The powder composition is inserted into the mold cavity as at least 5, preferably at least 9 casting inserts, wherein the spacing between the 4th and 5th, preferably the 8th and 9th casting inserts increases to at least 10 mm, preferably at least 12 mm.
9. Method for casting a component according to any one of the preceding claims, characterized in that The powder composition is inserted into the mold cavity and positioned so that the powder composition is in direct contact with at least one wall of the mold cavity and / or is spaced apart from a wall surface of the mold cavity.
10. A casting for use in a high wear industrial environment, the casting having a composite zone containing titanium carbide in a matrix material, the composite zone being formed in situ during the casting process of the molten host material and being obtained by using a powder composition, the powder composition comprising a reactive powder, the reactive powder forming titanium carbide in the composite zone and comprising titanium and carbon, and a conditioning powder, the conditioning powder forming a matrix around the titanium carbide in the composite zone and comprising a metal powder, characterized in that The main material weight of the casting is at least 30 kg, preferably at least 100 kg, and the wall thickness of the casting is at least 40 mm.
11. The casting according to claim 8, characterized in that The main body material is manganese cast steel, martensitic cast steel, cast iron, grey cast iron or white chrome cast iron.
12. The casting according to claim 8, characterized in that The weight of the main body material of the casting is at least 100 kg, the wall thickness of the casting is at least 80 mm, and the main body material is manganese cast steel or martensitic cast steel.
13. The casting according to claim 8, characterized in that The weight of the main material of the casting is at least 250 kg, the wall thickness of the casting is at least 80 mm, and the main material is manganese cast steel or martensitic cast steel.
14. The casting according to claim 8, characterized in that The weight of the main material of the casting is at least 600 kg, the wall thickness of the casting is at least 85 mm, and the main material is cast iron, gray cast iron or white chrome cast iron.
15. The casting according to claim 8, characterized in that The weight of the main material of the casting is at least 800 kg, the wall thickness of the casting is at least 50 mm, and the main material is manganese cast steel or martensitic cast steel.
16. A casting according to any one of claims 8 to 13, characterised in that The casting is a hammer, a plate hammer, a roll, a cone, a bowl, a plate, a screen lining, a pump trough or a pipe.
17. A powder composition for casting a component for use in a high wear industrial environment, the casting having a composite zone containing titanium carbide in a matrix material, the composite zone being formed in situ during the casting process of a molten host material and being obtained by using a powder composition, the powder composition comprising a reactive powder and a conditioning powder, the reactive powder forming titanium carbide in the composite zone and comprising titanium and carbon, the conditioning powder forming a matrix surrounding the titanium carbide in the composite zone and comprising a metal powder, characterized in that The powder composition consists of 55-80 wt.% of reaction powder and 20-45 wt.% of adjustment powder.
18. The powder composition according to claim 15, characterized in that The ratio of titanium to carbon in the reaction powder is 55 atomic %:45 atomic % or 45 atomic %:55 atomic % with an accuracy of 2%.
19. The powder composition according to claim 15 or 16, characterized in that The conditioning powder consists of a mixture comprising Fe, Mn, Si and C powders, preferably also comprising Cr powder.
Citation Information
Patent Citations
Powder composition for the manufacture of casting inserts, casting insert and method of obtaining local composite zones in castings
WO2017081665A1